Spatiotemporal Relationship of Brain Pathways during Human Fetal Development Using High-Angular Resolution Diffusion MR Imaging and Histology - Vasung, Lana; Raguz, Marina; Kostovic, Ivica; Takahashi, Emi (Frontiers in Neuroscience, 2017)
In this study, we aimed to identify major fiber pathways and their spatiotemporal relationships within transient fetal zones in the human fetal brain by comparing postmortem high-angular resolution diffusion MR imaging (HARDI) in combination with deterministic streamline tractography and histology. Diffusion weighted imaging was performed on postmortem human fetal brains (N=9, age=18-34 post-conceptual weeks (PCW)) that were grossly normal with no pathologic abnormalities. After HARDI was performed the fibers were reconstructed using deterministic streamline tractography. The position of major fiber pathways within transient fetal zones was identified both on diffusion images and histological sections. Our major findings include: 1) the development of massive projection fibers by 18 PCW, as compared to most association fibers (with the exception of limbic fibers) which have only begun to emerge 2) reconstructed fibers showed characteristic laminar distribution and sagittal plane geometry throughout development, 3) corpus callosum showed a protracted prenatal development, and 4) during an early prenatal period (24 PCW), radial coherence of the telencephalon predominated (i.e. majority of streamlines in the telencephalic wall were radially oriented). In conclusion, correlation between histology and HARDI (in combination with deterministic streamline tractography) allowed us to detect sequential development of fiber systems (projection, callosal, and association), their spatial relations with transient fetal zones, and their geometric properties.